Formulary Management Activities and Practice Implications Among Public Sector Hospital Pharmaceutical and Therapeutics Committees in a South African Province - Matlala, Moliehi; Gous, Andries G. S.; Meyer, Johanna C.; Godman, Brian (Frontiers in Pharmacology, 2020)
Introduction: The World Health Organisation identified Pharmaceutical and Therapeutics Committees (PTCs) at district and hospital levels as one of the pivotal models to promote rational use of medicines (RUM). This is endorsed by the Government in South Africa. Formulary development and management is one of the main functions of PTCs. This study aimed to describe the formulary management activities among PTCs in public hospitals in Gauteng Province, South Africa, following initiatives to promote RUM in South Africa Methods: Qualitative, non-participatory, observational method observing 26 PTC meetings. Data were coded and categorised using NVivo9® qualitative data analysis software. Themes and sub-themes were developed. The themes and sub-themes on formulary management are the principal focus of this paper. Results: More than half of the observed PTCs reviewed their formulary lists. There was variation in the review process amongst institutions providing different levels of care. Various aspects were considered for formulary management especially requests for medicines to be added. These included cost considerations (mainly focusing on acquisition costs), evidence-based evaluation of clinical trials, patient safety, clinical experience, and changes in the National Essential Medicines List (NEML). The Tertiary PTCs mostly dealt with applications for new non EML medicines, whilst PTCs in the other hospitals mainly requested removal or edition of EML medicines to the list. Conclusion: This is the first study from Gauteng Province, South Africa, reporting on how decisions are actually taken to include or exclude medicines onto formularies within public sector hospitals providing different levels of care. Various approaches are adopted at different levels of care when adding to- or removing medicines from the formulary lists. Future programmes should strengthen PTCs in specialised aspects of formulary management. A more structured approach to formulary review at the local PTC level should be encouraged in line with the national approach when reviewing possible additions to the NEML.